2021
DOI: 10.15252/msb.20209880
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of tyrosine recombinases allows annotation of mobile genetic elements in prokaryotic genomes

Abstract: Mobile genetic elements (MGEs) sequester and mobilize antibiotic resistance genes across bacterial genomes. Efficient and reliable identification of such elements is necessary to follow resistance spreading. However, automated tools for MGE identification are missing. Tyrosine recombinase (YR) proteins drive MGE mobilization and could provide markers for MGE detection, but they constitute a diverse family also involved in housekeeping functions. Here, we conducted a comprehensive survey of YRs from bacterial, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 121 publications
1
47
0
Order By: Relevance
“…The bacterial XerC are closely related to the resolvases that mediate dimer resolution of plasmids and some Tn3-like transposons ( Nicolas et al, 2015 ). Xer family recombinases are almost universal in bacteria and archaea ( Smyshlyaev et al, 2021 ), but appear to have been displaced by homologs from MGEs on several occasions. In particular, chromosome segregation in Streptococcus and Lactobacillus is effectuated by XerS, a resolvase more closely related to those of bacteriophages than it is to XerC ( Le Bourgeois et al, 2007 ; Cortez et al, 2010 ).…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial XerC are closely related to the resolvases that mediate dimer resolution of plasmids and some Tn3-like transposons ( Nicolas et al, 2015 ). Xer family recombinases are almost universal in bacteria and archaea ( Smyshlyaev et al, 2021 ), but appear to have been displaced by homologs from MGEs on several occasions. In particular, chromosome segregation in Streptococcus and Lactobacillus is effectuated by XerS, a resolvase more closely related to those of bacteriophages than it is to XerC ( Le Bourgeois et al, 2007 ; Cortez et al, 2010 ).…”
Section: Mainmentioning
confidence: 99%
“…MGEs also encode serine resolvases, which are unrelated to the tyrosine resolvases but play an analogous role ( Aravind et al, 2000 ; Midonet et al, 2014 ; Smyshlyaev et al, 2021 ). To our knowledge, there is currently no evidence that prokaryotic chromosome segregation is ever mediated by serine resolvases, despite their analogous functionality.…”
Section: Mainmentioning
confidence: 99%
“…ORF 77 encodes tyrosine recombinase that mediates unidirectional site-specific recombination between two DNA recognition sequences by mediating strand cleavage through catalyzing tyrosine (Groth and Calos, 2004 ). Other than that, tyrosine recombinases could protect genome integrity in phages by promoting post-replicative segregation of plasmids and circular chromosomes during cell division, and drive the movement of mobile genetic elements which can promote the phages' integration and transfer in bacterial genomes (Smyshlyaev et al, 2021 ). ORF188 encodes crossover junction endodeoxyribonuclease (RusA), which is involved in the viral processes of DNA replication, recombination, and repair (Mandal et al, 1993 ).…”
Section: Resultsmentioning
confidence: 99%
“…While providing a solution to the presence of accessory genes, such usage of large-scale public repositories may introduce poorly characterized or moonlighting (i.e., multifunctional) members of MGE protein families ( 35 37 ). For instance, Smyshlyaev et al demonstrated that the largest phylogenetic subgroup of tyrosine recombinases, a large protein family including phage and integron integrases, included the xerC/xerD family of simple tyrosine recombinases, which are infrequently associated with MGEs ( 38 ) ( Fig. 1C ).…”
Section: Introductionmentioning
confidence: 99%